2012
DOI: 10.5539/jas.v4n7p95
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fermentation Conditions for Antibiotic Production by Actinomycetes YJ1 Strain against Sclerotinia sclerotiorum

Abstract: In order to improve the productivity of activities substance of actinomycetes YJ1, the effects of the medium components, inoculation volume, medium capacity, rotary speed, fermentation time, temperature and initial pH on the biological activity of YJ1 were investigated by detecting the mycelium growth inhibition rate of Sclerotinia sclerotiorum. The results show that the inhibition rate is the highest under the optimum medium composition (g/L), containing sucrose 10.0, soluble starch 10.0, soybean meal 20.0, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 10 publications
3
23
0
1
Order By: Relevance
“…; Song et al. ). In this study, both fermentation conditions and medium components were optimized by RSM methods to effectively enhance the antifungal activities of S. lavendulae Xjy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Song et al. ). In this study, both fermentation conditions and medium components were optimized by RSM methods to effectively enhance the antifungal activities of S. lavendulae Xjy.…”
Section: Discussionmentioning
confidence: 98%
“…(P = 0.05). get maximum yield of antimicrobial metabolites (Ripa et al 2009;Kiranmayi et al 2011;Song et al 2012). In this study, both fermentation conditions and medium components were optimized by RSM methods to effectively enhance the antifungal activities of S. lavendulae Xjy.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the high cell density fermentations could be achieved by improving the oxygen conditions without affecting drastically the cellular physiological conditions (Verbelen et al 2009). However, in Actinomycetes YJ1 strain, the maximum antibiotic activity against Sclerotinia sclerotiorum was obtained at the inoculation volume of 5 %, while the antibiotic activity was not enhanced with the increases of pitching ratio (Song et al 2012). It was also demonstrated that the high pitching ratio (30 %, v/v) significantly enhanced the streptolydigin production of S. lydicus E9 (Cheng et al 2009).…”
Section: Discussionmentioning
confidence: 88%
“…Several actinomycetes require high amount of oxygen during the process of fermentation. Cultural medium contained organic and inorganic elements that lead to decrease in the level of dissolved oxygen; to meet this requirement there should be proper ventilation [26]. Temperature had great impact on production, during low temperature environmental pressure affected the secondary metabolites and resulted in amplified production [27].…”
Section: Fermentation Conditionsmentioning
confidence: 99%
“…The temperature affects the growth of actinomycetes. Favourable growth temperature is [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] C. Growth of the bacteria affected by the temperature and aeration that resulted influenced on the production of the antibiotics [28,29]. Another important factor that influences the production of the antibiotic is inoculum volume.…”
Section: Fermentation Conditionsmentioning
confidence: 99%